Multimedia interaktif Multimedia Interaktif “Belajar Kosa-Kata Bahasa Arab” Sebagai Media Edukasi Belajar Bahasa Arab Untuk Anak Sd Kelas IV - Kadariah Kadariah; Ahmad Hamim Thohari; Riwinoto Riwinoto (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2020)
Appropriate and appropriate learning methods in educating children are veryimportant things. With interactive multimedia technology that is widespread,we can use it as a learning media. Interactive multimedia development makesit possible to create an interactive educational media called "Learning ArabicVocabulary". The making of interactive multimedia "Learning Arabic Kosa-Kata" is designed based on a case study from the Elementary School (Al-Azhar Elementary School) that applies Arabic language learning. Using theright and varied media in the learning process can increase learningmotivation and can reduce student passivity (Hardianto,2005). Vocabularylearning is a very important material in language learning. A person will notbe able to speak a language before he enriches himself with vocabulary fromthat language. Likewise with children in this case. After the survey andinterview conducted at Al Azhar Elementary School located at Tiban 1,Patam Lestari, Kec. Sekupang, Batam City Prov. Riau Islands, on October31, 2018, the parties from the school in question were very hopeful that thisinteractive multimedia "Learning Arabic Kosa-Kata" could immediately beready for distribution.